Difficulty Learning Mathematics Material for Multiplication Counting Operations in Elementary School - Muthma'innah, M (Department of Mathematics, Universitas Negeri Padang (UNP), 2023)
Class III elementary school students are expected to be able to do multiplication sequentially both during the multiplication process and the accuracy of the results. However, students still do not fully understand the multiplication calculation operation, especially in a sequential way. This research aims to: 1) analyze the difficulties of learning mathematics in the Multiplication Calculation Operation material for class III students; 2) describe the factors causing these difficulties; 3) describe the efforts made to overcome these difficulties. This research includes qualitative research. The research results obtained: 1) Difficulty learning mathematical multiplication calculation operations experienced by class III Elementary School, namely: Difficulty understanding symbols, place value in multiplication, incorrect processes in multiplication, and calculations in multiplication; 2) Internal factors dominate the factors causing these difficulties; 3) Efforts made to overcome these difficulties are: the need to provide supporting training, guidance from teachers. This can be an essential note for teachers in mathematics and multiplication calculation operations. The impact of this research is as a consideration for mathematics teachers in teaching number multiplication material, as well as knowing more about the characteristics of students in solving number multiplication problems.